A just and civilised humanity: An integrative model between reformed theology and the ideology of Pancasila - Lumintang, Stevri P. N. I. (HTS teologiese studies, 2021)
This study aimed to produce a model of integration between theology (reformed) and ideology (Pancasila) to realise a just and civilised humanity (second sila of Pancasila). This research is based on the paradigm of naturalism with qualitative methods and the approach applied is historical and integrative. The research results produced an integrative model between Reformed Theology and the ideology of Pancasila that rejects the understanding and practice of capitalism, religious fundamentalism, communism, and racism. This study pointed out that these four understandings and practices contradict the basic principles of a just and civilised humanity based on theological and ideological studies.Contribution: This study produced four fundamental clues for all Indonesian citizens, especially Christians, namely the source, basis, pillars, and dual role as citizens and kingdoms of God in the fight for the formation of a just and civilised humanity.